Pengembangan Bahan Ajar E-Flipbook Berbantuan Aplikasi Flip PDF Corporate Edition Muatan IPS Kelas IV SDN 48 Cakranegara - Usman, Aulia; Dewi, Nurul Kemala; Indraswati, Dyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to produce valid and practical IPS content flipbook electronic teaching materials. This type of research is a 4-D model development research which consists of 4 stages, namely: define, design, develop and disseminate. The results of the eligibility validation of the media were 82.6% in the appropriate category and the results of the feasibility validation of teaching materials were 86.4% very feasible. The results of the teacher's response questionnaire were 90.27% very practical, the results of the student response questionnaire obtained an average of 88.8% in the very practical category. Thus it can be concluded that the development of social studies content flipbook electronic teaching materials for class IV SDN 48 Cakranegara is declared feasible and practical to use.